Bahasa, Agama, dan Konstruksi Budaya Hijau dalam Komunitas Ekonomi Lokal - Umar Mukhtar Siregar (Management Studies and Business journal, 2025)
This study explores the role of language and religion in constructing a green culture within local economic communities. Environmental degradation and economic vulnerability require approaches that integrate ecological values with culturally embedded meaning systems. Using a qualitative case study design, data were collected through observation, in-depth interviews, and document analysis involving local economic actors, religious leaders, and community figures. The findings reveal that religious language frames nature as a moral and spiritual trust, while religious teachings provide normative boundaries for economic activities. These discursive and ethical processes contribute to the formation of a green culture that influences production practices, marketing strategies, and consumption patterns. Green culture is manifested through restrained resource use, symbolic differentiation of products based on religious and ecological identity, and increased social trust toward environmentally responsible businesses. However, market pressures and structural economic constraints limit the consistent application of green values in practice. The novelty of this study lies in its integrative analysis of religious language and green culture as symbolic mechanisms that mediate between environmental ethics and local economic practices. The findings contribute to interdisciplinary discussions on language, religion, and sustainable local development by highlighting the importance of meaning-making processes in shaping ecological economic behavior.